2003
DOI: 10.1080/00380768.2003.10410016
|View full text |Cite
|
Sign up to set email alerts
|

Rubisco and nitrogen relationships in rice: Leaf photosynthesis and plant growth

Abstract: This review describes how ribulose-l,5-bisphosphate carboxylase (Rubisco) is related to photosynthesis, N economy, and whole plant growth in rice (Oryza sativa L.). Rubisco is a rate-limiting factor for potential photosynthesis under the present atmospheric air conditions. Although there is no variation in the enzymic properties of Rubisco among rice varieties including old and modern cultivars, the specific activity is 30 to 40% lower than that in other higher plants such as wheat, spinach, and tobacco. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 67 publications
3
59
0
1
Order By: Relevance
“…Grasses undergo progressive senescence where the older leaves senesce and are replaced by younger leaves on a continual basis. Photosynthetic rates at ambient CO2 levels scale with leaf Rubisco content [42], which increases rapidly during leaf emergence, reaches a peak around full expansion, and declines through until senescence [43,44]. However, even under high exogenous supply, approximately half of the nitrogen for new leaf growth comes from the remobilization of leaf proteins including Rubisco from older leaves [45].…”
Section: Plant Morphology As a Partial Consequence Of Photosynthetic mentioning
confidence: 99%
“…Grasses undergo progressive senescence where the older leaves senesce and are replaced by younger leaves on a continual basis. Photosynthetic rates at ambient CO2 levels scale with leaf Rubisco content [42], which increases rapidly during leaf emergence, reaches a peak around full expansion, and declines through until senescence [43,44]. However, even under high exogenous supply, approximately half of the nitrogen for new leaf growth comes from the remobilization of leaf proteins including Rubisco from older leaves [45].…”
Section: Plant Morphology As a Partial Consequence Of Photosynthetic mentioning
confidence: 99%
“…Numerous studies revealed a high positive correlation between light-saturated photosynthesis and nitrogen content in leaves of rice plants, since nitrogen invested in photosynthetically associated enzymes in chloroplasts accounts for a substantial part of leaf nitrogen content (Sinclair and Horie, 1989;Peng et al, 1995;Makino, 2003). Also, a higher stomatal conductance has been associated with a higher leaf photosynthetic rate (Wong et al, 1979;Kuroda and Kumura, 1990).…”
mentioning
confidence: 99%
“…The higher carbon gain in OM plants under well-watered conditions is likely due to the higher (P<0.01) total leaf area, which increased light interception ( Figure 2D) as previously reported by Vitale et al (2017) on tomato gown upon same conditions, rather than to an enhanced unit photosynthesis rate or to higher photosynthetic pigments and/or proteins content. In fact, the leaf-nitrogen content (Table 2), also related to Rubisco content (Makino, 2003) and Fv/Fm values (Table 3), related to functionality of photosystem 2 (Maxwell and Johnson, 2000), were comparable among treatments, thus suggesting that the unit photosynthetic rate was the same for all treatments.…”
Section: Plant Growth and Yieldmentioning
confidence: 87%